The correlational study about neutrophil-to-lymphocyte ratio and exercise tolerance of chronic obstructive pulmonary disease patients. Issue 33 (14th August 2020) - Yuan, Lindong; Li, Lili; Yu, Tong; Yang, Ziyun; Jiang, Tingting; Ma, Qiuxia; Qi, Jun; Shi, Yan; Zhao, Peige
Abstract : Abstract: To study the relationship between neutrophil to lymphocyte ratio (NLR) and exercise tolerance of patients with chronic obstructive pulmonary disease (COPD). 235 patients with COPD were selected as the study subjects. Complete blood count, C reactive protein (CRP), pulmonary function tests, the 6-minute walk distance (6MWD), Modified Medical Respiratory Council, the COPD assessment test, and clinical COPD questionnaire were tested. Heart rate, oxygen saturation, and Borg scale were tested before or after 6MWD test. By the median of NLR, the subjects were divided into 2 groups, NLR ≥4.5 group and NLR <4.5 group. The white blood cell count (WBC), CRP and deoxygenation saturation in the NLR ≥4.5 group were higher than those in the NLR <4.5 group, while the age, body mass index (BMI), 6MWD, and heart rate variation were lower than those in the NLR <4.5 group. CRP, WBC, and deoxygenation saturation had positive effects on NLR, BMI, 6MWT, and heart rate variation had negative effects on NLR. The Pearson correlation analysis showed NLR was positively correlated with WBC, CRP, BMI index, 6MWT, and deoxygenation saturation, while it was negatively correlated with BMI and heart rate variation. NLR might associate with exercise tolerance and cardiorespiratory reserve of COPD patients, and could be used as an indicator of muscle function in COPD patients.